Explaining the changes in procrastination in an ACT-based course – psychological flexibility and time and effort management as mediators - Asikainen, Henna; Hailikari, Telle; Katajavuori, Nina (Frontiers in Psychology, 2024)
Introduction The aim of our study is to explore the relationship between procrastination, time management skills and psychological flexibility and the changes in them during an Acceptance and Commitment therapy (ACT)-based course that included time management training. We also explored the effects of time management skills and psychological flexibility on procrastination. The study used an experimental design in an ACT-based well-being course that included time management training. Methods The participants were 109 students taking the course and 27 waiting list students. Analyses were conducted with Pearson correlation, mixed ANOVA and causal mediation analysis. Results and discussion Our results show that time management skills, psychological flexibility and procrastination were related to each other, and all changed during the course. In addition, change in both time management and psychological flexibility had an impact on the change in procrastination during the course. The results show that both time management and psychological flexibility influence the change in procrastination during an ACT-based course.